Efficacy and Biomarker Exploration of Sintilimab Combined With Chemotherapy in the Treatment of Advanced Penile Squamous Cell Carcinoma—A Report of Two Cases - Mei, Xinkuan; Zhao, Yanyan; Zhang, Yiruo; Liao, Jinhua; Jiang, Chen; Qian, Hesheng; Du, Yingying (Frontiers in Oncology, 2022)
Penile squamous cell carcinoma is a rare malignant tumor of the male reproductive system. We report two cases of advanced penile squamous cell carcinoma with persistent partial response/complete response after sintilimab combined with chemotherapy and analyze the relevant tumor biomarkers.